Innovation in chemistry learning: enhancing learning quality through training on the implementation of project- and game-based learning for the chemistry MGMP in Sidoarjo - Widarti, Hayuni Retno; Fauziah, Putri Nanda; Natasya, Shella; Sulistyorini, Dwi; Sumarsono, Raden Bambang; Setiawan, Nur Candra Eka; Minata, Zelen Surya; Rokhim, Deni Ainur (Journal of Saintech Transfer, 2025)
Students often consider chemistry as a difficult subject to understand because that most teachers still use conventional teaching methods and lack of application of innovative learning media. Along with the times, a student-centered learning approach is one of the potential innovations that can be applied in learning chemistry, such as project- and game-based learning. This community service aims to enhance teachers’ understanding and skills in implementing project-based learning and games in chemistry learning. The methods of this service are lectures and training. The subjects were 89 chemistry teachers from 40 high schools who are members of the Chemistry MGMP in Sidoarjo. The activities were carried out in the form of: (1) Socialization and sharing sessions on PjBL; (2) Socialization and sharing sessions on GBL; (3) Integration of project- and game-based learning in chemistry learning; (4) Demonstration of project- and game-based learning in chemistry learning; and (5) Sharing session on project-based teaching modules and games in chemistry learning. After participating in the activity, teachers’ understanding increased by 35.37%. This activity produces outputs in the form of best practices and teaching modules.